Proyecto de factibilidad para exportar cacao en polvo hacia el mercado de Pensilvania-Estados Unidos. (2022)
Colombia has climatic conditions and extensive fields, which are suitable for the production of cocoa and its transformation, where its cocoa has been recognized worldwide for its quality, where it is of the utmost importance to encourage the production and processing of cocoa. same.